The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1590/s1516-35982007000200011
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas de parâmetros genéticos e fenotípicos de características do pelame e de desempenho reprodutivo de vacas holandesas em clima tropical

Abstract: Gensys consultores associados S/S LTDA. 5 Doutor em Zootecnia.RESUMO -Objetivou-se investigar os efeitos das características do pelame sobre a idade ao primeiro parto (IPP) e o intervalo de partos (IEP) de vacas holandesas manejadas em sistema de estabulação livre com ventiladores e aspersores e estimar os parâmetros genéticos destas características. Os dados foram analisados pelo método dos quadrados mínimos, considerando os efeitos: ano; estação; número de inseminações; origem do pai; pai dentro da origem; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
6
1
4
Order By: Relevance
“…The heritability estimates for FCI (0.13 to 0.14) were not affected by the inclusion of short lactations; however, it showed slight superiority when model b was used. The values obtained in the present study were superior to those obtained by Val et al (2004), which were 0.10 for the Holstein breed; and Facó et al (2008), which were 0.05 for the Girolando breed, but inferior to the value obtained by Bertipaglia et al (2007) with Holstein cows (0.19).…”
Section: Discussioncontrasting
confidence: 83%
“…The heritability estimates for FCI (0.13 to 0.14) were not affected by the inclusion of short lactations; however, it showed slight superiority when model b was used. The values obtained in the present study were superior to those obtained by Val et al (2004), which were 0.10 for the Holstein breed; and Facó et al (2008), which were 0.05 for the Girolando breed, but inferior to the value obtained by Bertipaglia et al (2007) with Holstein cows (0.19).…”
Section: Discussioncontrasting
confidence: 83%
“…This protection differs according to many factors such as coat thickness (CT) and hair characteristics (Silva 2008;Maia et al 2009). Substantial research has been conducted to analyse the relationship between coat characteristics and livestock productivity and other traits that are not directly related to thermoregulation (Bertipaglia et al 2007(Bertipaglia et al , 2008. McManus et al (2009), analysing five sheep groups, found that animals that showed lower respiratory rate (RR), rectal temperature (RT) and heart rate are characterized by better coat traits to heat adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The animals, in general, are adaptable, able to maintain the life and performance in a wide range of physical, chemical, biological and social environments (BERTIPAGLIA et al, 2007). However, the understanding of the relationship between the animal and the complex environmental interactions is not yet fully defined .…”
Section: Introductionmentioning
confidence: 99%